PENGARUH PAJAK DAERAH, LABA BUMD TERHADAP PAD KABUPATEN/KOTA DI PROVINSI SUMATERA SELATAN - Eka Meiliya Dona; Agnes Widya Putri; Anis Feblin; Gitta Destalya Andrian Nova (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2022)
This study aims to determine the Influence of Regional Taxes, Profits of Regional Owned Enterprises (BUMD) on Regency/City Original Revenues in South Sumatra Province for the 2016-2020 period, either partially or simultaneously. This type of research used quantitative research. The data used in this study was secondary data sourced from www.djpk.kemekeu.go.id. The population in this study were 17 districts/cities in the province of South Sumatra. The analytical tool used in this research was multiple linear regression. The results of this study indicated that partially, the local tax variable had a positive or significant influence on local revenue. While the variable Profit of Regional Owned Enterprises (BUMD) had a positive or significant influence on Regional Original Revenues. Meanwhile, Simultaneously, the Regional Tax, Profit of Regional Owned Enterprises (BUMD) had a significant influence on Regional Original Revenues. The results of the coefficient of determination R Square showed 0.858, meaning that the magnitude of the contribution or the magnitude of the influence of the independent variable, namely Regional Tax, Profit of Regional Owned Enterprises (BUMD) on the dependent variable, namely Regency / City Original Revenue in South Sumatra Province for five years was 85.8% while the remaining 14.2% was determined by other variables that were not included in this research model such as regional levies and other legitimate income.